Disappearing teeth. The story of infra-occlusion of primary molars: diagnosis, aetiology and management. (2nd April 2023) - Hamilton, Sean; Oliver, Graham; Chawla, Ourvinder; Atack, Nicola E
Abstract : This article outlines the aetiology, diagnosis and treatment options available for the management of infra-occluded primary molars. Treatment decisions are mainly guided by the clinical presentation of the infra-occluded tooth, the malocclusion, the age of the patient, the presence or absence of the permanent successor and, of course, the wishes of the patient and/or parents. CPD/Clinical Relevance: It is important that infra-occlusion is diagnosed and managed in a timely way to prevent potentially avoidable complications.